Ginsenoside-Rp1 inhibits radiation-induced effects in lipopolysaccharide-stimulated J774A.1 macrophages and suppresses phenotypic variation in CT26 colon cancer cells - Baik, Ji Sue (J Ginseng Res, 2020)
This study investigated the inhibitory effect of ginsenoside-Rp1 (G-Rp1) on the ionizing radiation (IR)-induced response in lipopolysaccharide (LPS)-stimulated macrophages and its effects on the malignancy of tumor cells. G-Rp1 inhibited the activation of IR-induced DNA damage-related signaling molecules and thereby interfered with the IR-increased production of nitric oxide (NO) and interleukin (IL)-1β. The inhibitory effect of G-Rp1 increased the survival rate of mice inoculated with CT26 colon cancer cells by suppressing the phenotypic variation of tumor cells induced by conditioned medium obtained from IR- and LPS-treated J774A.1 macrophages.